2017
DOI: 10.1186/s12883-017-0801-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ABCB1 3435TT genotype and antiepileptic drugs resistance in Epilepsy: updated systematic review and meta-analysis

Abstract: BackgroundAntiepileptic drugs (AEDs) are effective medications available for epilepsy. However, many patients do not respond to this treatment and become resistant. Genetic polymorphisms may be involved in the variation of AEDs response. Therefore, we conducted an updated systematic review and a meta-analysis to investigate the contribution of the genetic profile on epilepsy drug resistance.MethodsWe proceeded to the selection of eligible studies related to the associations of polymorphisms with resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 99 publications
1
34
1
2
Order By: Relevance
“…Many further single and multiple SNP-based associations were published of different patient groups, varying case and control definitions, and, generally, small sample sizes. Some studies supported the original association, whereas others did not; meta-analyses of many such studies remain equivocal (Haerian et al, 2011;Sun et al, 2014;Chouchi et al, 2017), but it is still the case that the correctly designed, adequately controlled, and credibly powered study has not yet been undertaken. There are no common genetic variants associated with drug resistance currently in use to predict this phenotype.…”
Section: F Gene Variant Hypothesismentioning
confidence: 99%
“…Many further single and multiple SNP-based associations were published of different patient groups, varying case and control definitions, and, generally, small sample sizes. Some studies supported the original association, whereas others did not; meta-analyses of many such studies remain equivocal (Haerian et al, 2011;Sun et al, 2014;Chouchi et al, 2017), but it is still the case that the correctly designed, adequately controlled, and credibly powered study has not yet been undertaken. There are no common genetic variants associated with drug resistance currently in use to predict this phenotype.…”
Section: F Gene Variant Hypothesismentioning
confidence: 99%
“…These varied results of studies that involved different ethnic groups or races should consequently consider the study of ABCB1 haplotype or diplotype that represents the functional unit of the gene [11]. Meanwhile, a systematic review and metaanalysis of 13 studies involving a total of 454 patients with AED-resistant epilepsy and 282 response-to-AEDs indicated that TT genotype of ABCB1 C3435T played an important role in the incidence of refractory epilepsy [49].…”
Section: Resultsmentioning
confidence: 99%
“…Most recent studies continue to provide evidence of significant associations between drug resistance and ABCB1 3435 genotypes [36] . In addition, the results of a recent meta-analysis indicates that ABCB1 C3435T polymorphism, especially TT genotype, plays an important role in refractory epilepsy; the authors suggest that genetic screening of this genotype, before starting the treatment, may be useful to predict AED response [37] . Studies of gene variants for other transporter proteins such as multidrugresistanceassociated protein 2 (MRP2)/ABCC2 failed to provide evidence for a clinical impact of these tests in epilepsy therapy [38,39] .…”
Section: Pharmacoresistancementioning
confidence: 99%